(untitled) (Res Gesta, 2025)
The purpose of this article is, first, to reflect on the significance and impact of correspondence among intellectuals in the shaping and circulation of ideas, whether aesthetic, political, or more broadly cultural. A further aim concerns the formation of intellectual networks, which can be observed in epistolary exchanges. In this regard, we seek to examine more closely the role of affectivity within an Ibero-American network. In other words, we consider the emotions experienced collectively, which may take on a dual or a collective dimension when situated within the framework of a network.